Awareness about Cotton Production Technology of Tribal Farmer (Indian Journal of Extension Education, 2011)
Cotton (Gossypium hirsutum L.) is one of the most important fiber and commercial crop playing a key role in economic, political and social affairs in our country as well as world. India has the largest area 8.9 million hectare under cotton and contributes 69.09 percent of the total production. Cotton is an important case crop of Madhya Pradesh and occupies an area of 5.20 lake hectares. The main cotton growing area in Madhya Pradesh is East and West Nimarh (Khandwa, Khargone, Barwani) and Jhabua hills (Jhabua and Alirajpur distirict). Jhabua district is one of the main cotton-growing tracks. To achieve the higher level of production and productivity the inadequate level of knowledge of the recommended technology as well as its non-adoption may be a big hindrance which also hampers the production potential of the cotton crops. The gap always appears between the recommended technologies and there use in farmer’s field. Besides this agro-economic, socio-psychological characteristics of the farmers pay a major role in their knowledge and adoption for increasing production in tribal are further it is necessary to priorities strategy to increase the knowledge and adoption level of the tribes.